2011
DOI: 10.1002/elan.201100088
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electron Transfer Rates by AC Voltammetry for Ferrocenes Attached to the End of Embedded Carbon Nanofiber Nanoelectrode Arrays

Abstract: The effect of the interior structure of carbon nanomaterials on their electrochemical properties is not well understood. We report here the electron transfer rate (ETR) of ferrocene (Fc) molecules covalently attached to the exposed end of carbon nanofibers (CNFs) in an embedded nanoelectrode array. The ETR in normal DC voltammetry was found to be limited by the conical graphitic stacking structure interior of CNFs. AC voltammetry, however, can cope with this intrinsic materials property and provide over 100 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
(55 reference statements)
3
15
0
Order By: Relevance
“…Using VACNF NEAs, the optimum frequency for Fc through a short NH 2 CH 2 -linker was found to be 40 times higher than macroscopic glassy carbon electrode (GCE). 17 Similar phenomena were also observed with Fc attached to the electrode surface through a tetrapeptide and linker groups, i.e. H 2 N-(CH 2 ) 4 -CO-Ala-Ala-Asn-LeuNHCH 2 -Fc.…”
Section: Acv Electrochemical Biosensor For Proteasesupporting
confidence: 57%
See 2 more Smart Citations
“…Using VACNF NEAs, the optimum frequency for Fc through a short NH 2 CH 2 -linker was found to be 40 times higher than macroscopic glassy carbon electrode (GCE). 17 Similar phenomena were also observed with Fc attached to the electrode surface through a tetrapeptide and linker groups, i.e. H 2 N-(CH 2 ) 4 -CO-Ala-Ala-Asn-LeuNHCH 2 -Fc.…”
Section: Acv Electrochemical Biosensor For Proteasesupporting
confidence: 57%
“…Recently, we found that ACV measurements on CNF NEAs have a distinct advantage over commonly used CV techniques which is based on direct current (DC) ramping. 17 An anomalously high electron transfer rate was obtained with redox-active ferrocene (Fc) molecules attached to the exposed CNF tips of an embedded NEA. 17 This is likely attributed to the unique conically stacked graphitic structure of the CNFs in the NEA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15, 16, 22 According to our previous study, the variation can be normalized by using the relative change represented by the “extracted proteolytic signal” S, as defined below: 15 …”
Section: Resultsmentioning
confidence: 99%
“…The unique structure of VACNFs allowed using a high-frequency (∼1 kHz) alternating current voltammetry (ACV) to monitor the small electrochemical signal from Fc. 14-16 In this report, we further apply this technique on detection of cathepsin B activities in four types of cell lysates including normal and breast cancer cells. The cathepsin B activities were found increased from normal to cancer cells and reached highest value in metastatic cancer cell lysate.…”
Section: Introductionmentioning
confidence: 99%